Intelligence in an insecure world - Gill, Peter; Phythian, Mark (Polity Press, 2018)
In this third edition of their classic guide to the field, Gill and Phythian set out a comprehensive framework for the study of intelligence, discussing how states organise the collection, analysis and dissemination of intelligence, how it is acted upon, why it may fail and how the process should be governed in order to uphold democratic rights.